2006
DOI: 10.1111/j.1365-4632.2006.02741.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological characteristics of poroid neoplasms: a study of 25 cases in Taiwan

Abstract: PNs are sudoriferous tumors that may vary considerably in clinical expression. EP, about 64% (16/25) of PNs in our series, was the most common. PH incidence is probably underestimated in the literature. We found six PHs in 25 PNs. Histopathologically, it is not justified to exclude PN diagnosis by noticing horn cysts. It was uncommon for two or three subtypes of PN to occur in a single lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 16 publications
1
55
1
Order By: Relevance
“…1 ''Hybrid'' lesions featuring a combination of 2 or more of these poroid neoplasms have been reported. 2,3 Traditionally, poroid neoplasms were considered eccrine. However, several reports documenting features of true apocrine secretion or the presence of sebaceous and/or follicular differentiation in poroma lead to the introduction of the term ''apocrine poroma.''…”
Section: Introductionmentioning
confidence: 99%
“…1 ''Hybrid'' lesions featuring a combination of 2 or more of these poroid neoplasms have been reported. 2,3 Traditionally, poroid neoplasms were considered eccrine. However, several reports documenting features of true apocrine secretion or the presence of sebaceous and/or follicular differentiation in poroma lead to the introduction of the term ''apocrine poroma.''…”
Section: Introductionmentioning
confidence: 99%
“…Battistella and co-workers 14 P + HS) among 25 tumors. 13 On the other hand, in this study, among the 384 cases we diagnosed 198 P (51.6%), 20 HS (5.2%), five D (1.3%), 56 HA (14.6%) and 105 (27.3%) composite tumors. In our study, D and P were fewer, but composite tumors were more frequently observed than in the report of Battistella et al 14 Although we cannot clearly explain such difference, we might make more strict diagnoses of each subtypes in poroid neoplasms.…”
Section: Discussionmentioning
confidence: 42%
“…In all subtypes, female cases were more frequent, even in HS that has been reported to have a male predominance. 13 Age at resection of female cases was a little higher than that of male cases. Battistella et al reported that age at resection of HS cases was higher than that of other subtypes; 5,7,14 however, in this study, that of all subtypes were almost equal.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Histologically the features of an eccrine poroma are a monomorphic proliferation of poroid and cuticular cells, with ductular differentiation and multiple points of epidermal origin [5]. Its aetiology is unknown; however, it is postulated that the following may be causative factors: solar damage, radiation exposure, trauma, and human papilloma virus [6].…”
Section: Answermentioning
confidence: 99%